Regioselective synthesis of 7,8-dihydroimidazo[5,1-c][1,2,4]triazine-3,6(2H,4H)-dione derivatives: A new drug-like heterocyclic scaffold - Tzvetkov, Nikolay T.; Euler, Harald; Müller, Christa E. (Beilstein Journal of Organic Chemistry, 2012)
Dihydroimidazo[5,1-c][1,2,4]triazine-3,6(2H,4H)-dione derivatives were prepared by successive N3- and N1-alkylation of hydantoins, followed by regioselective thionation and subsequent cyclization under mild conditions. In a final alkylation step a further substituent may be introduced. The synthetic strategy allows broad structural variation of this new drug-like heterobicyclic scaffold. In addition to extensive NMR and MS analyses, the structure of one derivative was confirmed by X-ray crystallography.
Keywords: hydantoins; hydrazides; imidazotriazines; N-alkylation; regio- and chemoselective reaction; thionation; X-ray structure